(3GdeNJGQ ef SbW GdRfOs - (3eLghds; (3CHh GdYdGA GdeYQj , CHh GdYdGA CMeO Hf YHO Gddg Hf SdjeGf GdJfhMj GdeYQj,J (B449 (3g` s
(3ChdgG (B:s
(3CYfj hNP GdbdGMj cTaJ MGdG hef YfO GdXdGe WdHJ MGdkG hoOqQQG pNdJ CfLeg Ydjg agdqG NdJgf Hg PHGdG s
(3BNQgG (B:s
(3EPG LGhQJgG fHPJ LhGQj hEdG oJda dj PfHG JLfg JeJ GdeNJGQGJ ef SbW GdRfO, dCHj GdYdGA GdeYQj hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B157 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B290s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B25 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B992s
Keywords: (3GdCOHs